MOBILIZATION AND STABILIZATION OF SAND DUNES IN HUMID AND ARID CLIMATES - Tsoar, Haim; Arens, Sebastiaan M. (Mercator, 2008)
Coastal sand dunes form an important and unique system that can be mobile or fixed. Vegetation on sand dunes is known to be meagre and does not increase with increase in rainfall and temperature as it does with plants on other soils. The reasons for such are the big pore spaces of sand and the low percentage of soil moisture at field capacity that allow easy infiltration to the ground table, and the lack of cohesion of the sand that makes wind erosion the main limiting factor for vegetation. In this study the climatic factors of the hot arid Negev fixed sand dunes and the tempest humid Dutch coastal dunes that were activated artificially, are compared. Vegetation did not recover in the Netherlands more than four years after it was removed, while in the Negev Desert they recovered after such a spell. The main difference between the two dune fields lies in the amount of wind power, manifested by the drift potential (DP), which is responsible for the limiting factor of plants on sand. The physical – biological interaction is further developed by a hysteresis, which shows that a dune can become vegetated when the wind power is sufficiently low. Once vegetated, a much higher wind stress is needed to destroy the vegetation and re-activate the dunes.Vegetation can cover sand dunes that are under high wind power only if they were planted artificially as was the case in most of the European coastal dunes. These dunes are in a stable state once the vegetation is removed because of the high DP. The effect of climate change on sand dunes is reflected primarily by the change in wind power and not by a change in rainfall and temperature.